Current state of evidence and future direction for Knowledge Attitude and Practice studies in antimicrobial resistance - a novel conceptual framework - Miss Alison Shutt; Dr Arunima Sehgal Mukherjee; Dr Vrinda Nampoothiri; Professor Alison Holmes; Associate Professor Esmita Charani (International Journal of Infectious Diseases)
Introduction: Antimicrobial resistance (AMR) is a global emergency requiring a multi-disciplinary approach with contextualised knowledge and solutions. Current evidence demonstrates inequities in the burden of AMR. Social determinants of health (SDoH) and individual factors including gender, race, ethnicity and socio-economic status impact AMR risk, especially in Low and Low - middle income countries. In 2015 the World Health Organisation recommended global AMR awareness campaigns with assessment of people's knowledge of AMR, antibiotics and associated behaviours. Evidence from existing knowledge, attitude and practice (KAP) studies was evaluated for gaps and opportunities to provide future direction in this field. Methods: KAP studies that considered the intersection of SDoH with AMR and drug resistant infections were retrieved using systematic review methodology. Ovid MEDLINE, Ovid EMBASE, the Cochrane Library, PsycINFO and Scopus were searched for published evidence between 2000-2022 in the English language. An analysis of Strengths, Weaknesses, Opportunities and Threats was performed to map the recommendations from the KAP studies for suitability against the target populations. Results: Of the 40 KAP studies, 24/40 (60%) were quantitative, 12/40 (30%) were qualitative, and 4/40 (10%) were mixed methods. Studies were from High 14/40 (35%), Low-middle 13/40 (32.5%), Upper-middle 8/40 (20%) and Low 5/40 (12.5%) income countries. Across all studies, a lack of knowledge about AMR and antibiotics was reported. The studies provide evidence about the practice of self-medication, methods for obtaining antibiotics and the respective social, cultural and economic drivers for this behaviour. The majority of recommendations focus on continued health education campaigns and strengthening enforcement of regulation for access to antibiotics. This approach is perpetuated despite evidence demonstrating that people's behaviour may not be changed following health education programmes. There is a gap in recognising that structural, environmental, and socioeconomic drivers including proximity and ease of accessing health services require urgent attention to change antibiotic use behaviours of individuals. Discussion: Whilst existing KAP studies on AMR answer “what” is happening they do not address the “why”, especially in relation to SDoH and cultural contexts. Research must now focus on understanding the upstream factors, rather than focussing on the individuals who often have little control over the burden of inequalities, social and structural, they are subjected due to SDoH. Maslow's hierarchy of needs illustrates that people cannot progress if their basic resources are not available. It is argued that the practice of self-medication will continue to occur if structural, social and environmental needs are not met. Conclusion: KAP studies need to be refocused by considering the SDoH using a universal set of indicators that factor in the structural and environmental needs of people at greatest risk of AMR infection and spread.